Efficacy and safety of live combined Bacillus subtilis and Enterococcus faecium in patients with constipation: a meta-analysis of randomized controlled trials - Li, Wenwen; Liang, Yingying; Li, Guangcai; Yang, Dandan; Zhang, Xiaoqian (Frontiers in Pharmacology, 2025)
BackgroundLive combined Bacillus subtilis and Enterococcus faecium (LCBE) provides favorable clinical benefits in patients with constipation, although a comprehensive evaluation is lacking. This meta-analysis aimed to thoroughly evaluate the efficacy and safety of LCBE in patients with constipation.MethodsRandomized controlled trials (RCTs) assessing the efficacy or safety of LCBE in patients with constipation, published before September 2025, were comprehensively searched for in Wan Fang, China National Knowledge Infrastructure, China Science and Technology Journal Database, Web of Science, Cochrane Library, and PubMed. Efficacy and safety outcomes were extracted.ResultsA total of 32 studies were included, containing 1,565 patients receiving LCBE and control treatment (experimental group) and 1,490 patients receiving control treatment alone (control group). The experimental group showed a higher total effective rate [odds ratio (OR) (95% confidence interval (CI)) = 5.789 (4.598–7.288); p < 0.001], Bristol Stool Scale score [standardized mean difference (SMD) (95% CI) = 2.532 (1.274–3.790); p < 0.001], defecation frequency per week [SMD (95% CI) = 1.937 (1.252–2.623); p < 0.001], and defecation rate within 24 h [OR (95% CI) = 2.545 (1.377–4.705); p = 0.003] than the control group. The defecation difficulty score tended to decrease in the experimental group relative to that in the control group, although this did not reach statistical significance [SMD (95% CI) = −1.924 (−3.947 to 0.099); p = 0.062]. There was no difference in the total adverse reaction rate between groups [OR (95% CI) = 0.703 (0.414–1.191); p = 0.190]. Subgroup analyses suggested that LCBE was effective, regardless of dosage form or treatment course. All studies were of moderate-to-high quality.ConclusionLCBE demonstrates a favorable efficacy and good tolerability in patients with constipation. This meta-analysis provides supportive evidence for its clinical application in the management of constipation.